2012
DOI: 10.1097/shk.0b013e31825ad7af
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Hemoglobin Attenuates Cardiac Dysfunction and Sympathetic Activity During Hypohemoglobinemic Shock

Abstract: The use of liposome-encapsulated hemoglobin (LHb), which is a cellular Hb, has been demonstrated to be beneficial in the treatment of hypohemoglobinemic shock. As a molecule of appropriate size (220 nm) that can carry oxygen, LHb may ameliorate cardiac dysfunction during lethal hemodilation. The purpose of this study was to determine the efficacy of LHb transfusion in relieving cardiovascular dysfunction in a rat model of lethal progressive hemodilution. Over the course of 150 min, rats were subjected to blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The results of the present study are in agreement with those of our previous reports 23,29,30 and other reports of prototypic cellular Hbs and acellular Hbs. 23,30 In our previous reports that used the same 85% hemodilution lethal massive hemorrhagic shock model, the prototype cellular Hb, which is similar to HbV, improved the prognosis and ameliorated organ damage comparably to wRBC, 23 and showed a significant salutary effect on cardiac autonomic function and the condition of the heart. 30 However, this previous study did not investigate the mechanism of this favorable effect on the heart, especially arrhythmogenesis.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The results of the present study are in agreement with those of our previous reports 23,29,30 and other reports of prototypic cellular Hbs and acellular Hbs. 23,30 In our previous reports that used the same 85% hemodilution lethal massive hemorrhagic shock model, the prototype cellular Hb, which is similar to HbV, improved the prognosis and ameliorated organ damage comparably to wRBC, 23 and showed a significant salutary effect on cardiac autonomic function and the condition of the heart. 30 However, this previous study did not investigate the mechanism of this favorable effect on the heart, especially arrhythmogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…Third, to investigate the protective effect of HbV on myocardium in severe hemorrhage, the measurements of the blood levels of troponin and/or CK‐MB are important, but we could not measure these parameters. We previously measured heart‐type fatty acid‐binding protein which is a similar biomarker to troponin and CK‐MB in a severe hemorrhagic model and we showed that prototypic cellular Hbs prevented the leakage of heart‐type fatty acid‐binding protein from the heart 30 . We speculate that HbV has the same effects on the troponin and CK‐MB.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, according to a clinical study, 18 relatively longer periods after the occurrence of prolonged cardiac ischemia are required before these abnormal levels are detected; therefore, these parameters were not measured in this study. However, we previously measured heart‐type fatty acid–binding protein, which is detected much earlier than troponin or CK‐MB, and demonstrated that prototypic cellular Hb ameliorated the blood levels of heart‐type fatty acid–binding protein 19 …”
Section: Discussionmentioning
confidence: 99%